Serial Within-Session Improvements in Ankle Dorsiflexion During Clinical Interventions Including Mobilization-With-Movement and A Novel Manipulation Intervention – A Case Series - Mohsen Abassi; Rod Whiteley (International Journal of Sports Physical Therapy)
# Background